Pairing in the BCS and LN approximations using continuum single particle level density - Id Betan, Rodolfo Mohamed (2017)
Understanding the properties of drip line nuclei requires to take into account the correlations with the continuum spectrum of energy of the system. This paper has the purpose to show that the continuum single particle level density is a convenient way to consider the pairing correlation in the continuum. Isospin mean-field and isospin pairing strength are used to find the Bardeen–Cooper–Schrieffer (BCS) and Lipkin–Nogami (LN) approximate solutions of the pairing Hamiltonian. Several physical properties of the whole chain of the Tin isotope, as gap parameter, Fermi level, binding energy, and one- and two-neutron separation energies, were calculated and compared with other methods and with experimental data when they exist. It is shown that the use of the continuum single particle level density is an economical way to include explicitly the correlations with the continuum spectrum of energy in large scale mass calculation. It is also shown that the computed properties are in good agreement with experimental data and with more sophisticated treatment of the pairing interaction.